Association of Human Capital with Physical Growth from Birth to Adulthood : Evidence from the New Delhi Birth Cohort, India - Sachdev, Harshpal Singh; Kathuria, Ashi Kohli; Sinha, Sikha; Anand, Deepika; Bhargava, Santosh K. (World Bank, Washington, DC, 2020)
Undernutrition begins early in life and has lifelong consequences. The cost of undernutrition both for the individual and the economy are substantial. Analyzing data from an Indian cohort, the New Delhi Birth Cohort, formed between 1969 and 1972, this paper provides evidence on the associations between attained human capital in the third and fourth decade of life and measures of growth from birth to adulthood. For the purpose of this paper, attained human capital is defined through three metrics: educational status, male occupation, and material possession score. Growth measures (height, weight, body mass index (BMI)) during five age intervals (0 to 6 months, 6 to 24 months, 2 to 5 years, 5 to 11 years, and 11 years to adulthood) were related to human capital metrics using multivariate regression models. Sensitivity analyses were also performed to assess the stability of associations. All three human capital metrics had a significant positive association with birth size and measures of physical growth in children under-five years of age, in particular for children under two years. Length at birth and height gain from 6 to 24 months were consistently associated with all metrics. Faster weight and BMI gain from five years onward significantly predicted material possession scores. Among socioeconomic and behavioral characteristics at birth, maternal and paternal education, and paternal occupation also had a consistent positive association with all three human capital metrics. The findings reinforce the focus on interventions during the first 1,000 days of life to promote larger birth size and linear growth and suggest an additional window of opportunity between 2 to 5 years to improve human capital. The benefits can be enhanced by simultaneous investments in parental (especially maternal) literacy, livelihoods, safe water supply and sanitation, access to health care, and enhancing incomes. These interventions also have a nutrition-sensitive effect to promote early life growth.